Translations of Foreign Poetry. Translation of Giambattista Marino's Poetry into Ukrainian (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
Motovylovets M. Translation of Giambattista Marino's Poetry into Ukrainian